Studying the composition and mineralogy of the hermean surface with the Mercury Radiometer and Thermal Infrared Spectrometer (MERTIS) for the BepiColombo mission: an update - Hiesinger, H; Helbert, J; Alemanno, G; Bauch, KE; D’Amore, M; Maturilli, A; Morlok, A; Reitze, MP; Stangarone, C; Stojic, AN; Varatharajan, I; Weber, I; et al. (Springer, 2020)
Launched onboard the BepiColombo Mercury Planetary Orbiter (MPO) in October 2018, the Mercury Radiometer and Thermal Infrared Spectrometer (MERTIS) is on its way to planet Mercury. MERTIS consists of a push-broom IR-spectrometer (TIS) and a radiometer (TIR), which operate in the wavelength regions of 7-14 μm and 7-40 μm, respectively. This wavelength region is characterized by several diagnostic spectral signatures: the Christiansen feature (CF), Reststrahlen bands (RB), and the Transparency feature (TF), which will allow us to identify and map rock-forming silicates, sulfides as well as other minerals. Thus, the instrument is particularly well-suited to study the mineralogy and composition of the hermean surface at a spatial resolution of about 500 m globally and better than 500 m for approximately 5-10% of the surface. The instrument is fully functional onboard the BepiColombo spacecraft and exceeds all requirements (e.g., mass, power, performance). To prepare for the science phase at Mercury, the team developed an innovative operations plan to maximize the scientific output while at the same time saving spacecraft resources (e.g., data downlink). The upcoming fly-bys will be excellent opportunities to further test and adapt our software and operational procedures. In summary, the team is undertaking action at multiple levels, including performing a comprehensive suite of spectroscopic measurements in our laboratories on relevant analog materials, performing extensive spectral modeling, examining space weathering effects, and modeling the thermal behavior of the hermean surface.